2013
DOI: 10.1007/s11302-013-9371-6
|View full text |Cite
|
Sign up to set email alerts
|

CAY10593 inhibits the human P2X7 receptor independently of phospholipase D1 stimulation

Abstract: The P2X7 receptor is a trimeric ATP-gated cation channel important in health and disease. We have observed that the specific phospholipase D (PLD)1 antagonist, CAY10593 impairs P2X7-induced shedding of the 'low affinity' IgE receptor, CD23. The current study investigated the mode of action of this compound on P2X7 activation. Measurements of ATP-induced ethidium + uptake revealed that CAY10593 impaired P2X7-induced pore formation in human RPMI 8226 B cells, P2X7-transfected HEK-293 cells and peripheral blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, many of the original antagonists are subject to degradation when used in vivo or are predicted to have poor pharmacokinetics (Friedle et al, 2010;Jiang, 2012) , and N-(adamantan-1-ylmethyl)-5-[(3R-amino-pyrrolidin-1-yl)methyl]-2-chloro-benzamide (AACBA; also known as GSK314181) (Broom et al, 2008), the cyanoguanidine derivative (Honore et al, 2006), the cyclic imide 3- [1-[[(39-nitro[1,19-biphenyl]-4-yl)oxy]methyl]-3-(4-pyridinyl) propyl]-2,4-thiazolidinedione (AZ11645373) (Stokes et al, 2006), and the nicotinamide derivative N-([4-(4-phenyl-piperazin-1-yl]tetrahydro-2H-pyran-4-yl)-methyl)-2-(phenyl-thio) nicotinamide (JNJ-47965567) (Letavic et al, 2013). The concentration responses of some of these specific antagonists (including A438079 and AZ11645373) have been determined at native murine P2X7 receptors Pupovac et al, 2013b), which is useful for their in vivo application. However, despite the availability of these newer P2X7 antagonists, many in vivo studies still use first generation antagonists (see section X).…”
Section: Modulators Of P2x7 Receptor Activationmentioning
confidence: 99%
“…Furthermore, many of the original antagonists are subject to degradation when used in vivo or are predicted to have poor pharmacokinetics (Friedle et al, 2010;Jiang, 2012) , and N-(adamantan-1-ylmethyl)-5-[(3R-amino-pyrrolidin-1-yl)methyl]-2-chloro-benzamide (AACBA; also known as GSK314181) (Broom et al, 2008), the cyanoguanidine derivative (Honore et al, 2006), the cyclic imide 3- [1-[[(39-nitro[1,19-biphenyl]-4-yl)oxy]methyl]-3-(4-pyridinyl) propyl]-2,4-thiazolidinedione (AZ11645373) (Stokes et al, 2006), and the nicotinamide derivative N-([4-(4-phenyl-piperazin-1-yl]tetrahydro-2H-pyran-4-yl)-methyl)-2-(phenyl-thio) nicotinamide (JNJ-47965567) (Letavic et al, 2013). The concentration responses of some of these specific antagonists (including A438079 and AZ11645373) have been determined at native murine P2X7 receptors Pupovac et al, 2013b), which is useful for their in vivo application. However, despite the availability of these newer P2X7 antagonists, many in vivo studies still use first generation antagonists (see section X).…”
Section: Modulators Of P2x7 Receptor Activationmentioning
confidence: 99%
“…FIPI and the isoform-selective inhibitors have become widely used to explore roles for PLD in cells (11,13,21,34,(57)(58)(59)(60)(61)(62)(63)(64)(65). To date, the inhibitors have not been associated with off-target or nonspecific effects, excepting one of the PLD1-selective compounds (66). FIPI has also been employed in vivo to study cancer growth and metastasis and platelet activation (22,35,67), which was achievable given its 5.5 h half-life and acceptable bioavailability and solubility (54).…”
Section: Tools Used For Study Of Pld Functionmentioning
confidence: 99%
“…Studies of P2X7-induced CD23 shedding in RPMI 8226 cells indicated that neither K + efflux, Na + influx, Ca 2+ influx nor increases in intracellular Ca 2+ were essential for this process [45]. In fact, extracellular Ca 2+ partly impaired P2X7-induced CD23 shedding from CLL cells [34].…”
Section: Cd23 (Low Affinity Ige Receptor)mentioning
confidence: 99%
“…However the mechanism by which these divalent cations impair P2X7-induced CD23 shedding remains unknown. Finally, attempts using small molecule inhibitors in RPMI 8226 cells have failed to establish a role of many enzymes, commonly downstream of P2X7 activation, in P2X7-induced CD23 shedding including PKC, JNK, Rho kinase, PI3K, GSK-3, MAPK, acid sphingomyelinase and phospholipases [45].…”
Section: Cd23 (Low Affinity Ige Receptor)mentioning
confidence: 99%